Facebook i społeczne konstrukcje narcyzmu (o tożsamości zamkniętej w celi wizerunku) - Melosik, Zbyszko (Wydawnictwo Naukowe UAM, 2013)
The article is aimed at analysing the social role of Facebook in contemporary society, especially among young generation. Various contexts of this problem are considered against the background of image construction and self-presentation concept. Also, some social issues of Facebook use are taken into account.
Facebook and social construction of narcissism (some remarks on identity closed in the cell of imageclosed in the cell of image)
Keywords: Facebook; narcissism; image; self-presentation; happiness; hiperreality